THE USE OF AUTHENTIC MATERIALS IN ENGLISH LANGUAGE CLASSROOMS: BRIDGING THE GAP BETWEEN THEORY AND REAL- WORLD COMMUNICATION - Odilova Zuhrakhon (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract This research examines the pedagogical significance of integrating authentic materials into the English as a Foreign Language (EFL) classroom. Authentic materials—ranging from newspapers, podcasts, and brochures to films and advertisements—provide learners with exposure to the language as it is naturally used by native speakers. The study evaluates how these materials influence student motivation, cultural competence, and linguistic flexibility. By comparing "pedagogical" (textbook-based) texts with "authentic" sources, the research argues that the latter is essential for developing true communicative competence. The paper also outlines strategies for curriculum developers to select and adapt authentic content for diverse proficiency levels.